Self Concept and Learned Helplessness in a group of teachers from Lima Metropolitana - Carrillo Luna, Sandra (2001)
86 teachers from Lima Metropolitana trained by PLANCAD were assessed with the Self Perception Profile for Adult~ (Messer y Harter, 1986) and with a Learned Helplessness Scale (Macassi, 1988). Correlations between the different domains from Self Concept (SC), Learned Helplessness (LH) and sorne social-demographic variables were analyzed. The result~ showed that the LH exhibits significan! and inverse correlations with sorne domains of SC such a~: lntelligence, Job Competence (JC). Sociability, Adequate Provider (AP), Physical Appearance (PA), lntimate Relationships (IR), Academic Achievement (AA) and the Job Satisfaction Degree. They also showed significan! correlations between the variable age and two domains of SC: Sociability and IR; between Career Satisfaction and the SC domains of Sociability, AP, JC and IR; also between Job Satisfaction and the SC domains of lntelligence, Household Management, JC, AP, PA and IR. Finally significan! correlations were showed between Academic Achievement with the domain of Sociability. The results also showed significan! Differences between the punctuation obtained from the variables of sex, the institutions.